Phylogenomic Relationships and Evolution of Polyploid Salix Species Revealed by RAD Sequencing Data - Wagner, Natascha D.; He, Li; Hörandl, Elvira (Frontiers in Plant Science, 2020)
Polyploidy is common in the genus Salix. However, little is known about the origin, parentage and genomic composition of polyploid species because of a lack of suitable molecular markers and analysis tools. We established a phylogenomic framework including species of all described sections of Eurasian shrub willows. We analyseanalyzed the genomic composition of seven polyploid willow species in comparison to putative diploid parental species to draw conclusions on their origin and the effects of backcrossing and post-origin evolution. We applied recently developed programs like SNAPP, HyDe, and SNiPloid and to established a bioinformatic pipeline for unravelling the complexity of polyploid genomes. RAD sequencing revealed 23,393 loci and 320,010 high quality SNPs, to analyse for the analysis of the relationships of 35 species of Eurasian shrub willows (Salix subg. Chamaetia/Vetrix). Polyploid willow species appear to be predominantly of allopolyploid origin. More ancient allopolyploidization events were observed for two hexaploid and one octoploid species, while our data suggested a more recent allopolyploid origin for the included tetraploids and identified putative parental taxa. SNiPloid analyses disentangled the different genomic signatures resulting from hybrid origin, backcrossing, and secondary post-origin evolution in the polyploid species. Our RAD sequencing data demonstrate that willow genomes are shaped by ancient and recent reticulate evolution, polyploidization, and post-origin divergence of species.